Case controlled study for determination of risk factors in abdominal wall endometriosis following a cesarean section. Issue 3 (September 2022) - Erdoğan, Pınar; Erdoğan, Alirıza; Bolat, Hacı; Özbey, Caner
Introduction: Abdominal wall endometriosis (AWE) is the presence of ectopic endometrial tissue in abdominal wall and is most frequently encountered in women with previous cesarean section (CS). The aim of this study is to evaluate the possible risk factors of AWE development. Methods: Women with previous CS and pathologically confirmed AWE were included into the study ( n = 33). Controls ( n = 127) were randomly selected among women who had previous CS and absence of AWE were confirmed by physical examination. Clinical characteristics of the patient and the CS operation preceding AWE were recorded. Results: CS was performed before onset of labor in 87.9% in AWE and in 59.1% of control group ( p = 0.002). The antenatal BMI and weight gain during pregnancy were significantly higher in AWE patients ( p < 0.0001; p = 0.002, respectively). In logistic regression model procedure duration ( p = 0.039; OR = 1083), antenatal BMI ( p = 0.003; OR = 1254), weight gain ( p = 0.002; OR = 1171), and CS before spontaneous labor ( p = 0.021; OR = 5169) were significant parameters for predicting AWE. Discussion: High antenatal BMI, weight gain during pregnancy, and longer duration of operation are all factors effecting subsequent AWE development. However, CS before spontaneous labor is by far the most powerful risk factor for AWE development.